2002
DOI: 10.4049/jimmunol.168.5.2111
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of In Vivo Priming of CD4 and CD8 T Cells by Dendritic/Tumor Fusion Cells in MUC1-Transgenic Mice

Abstract: Previous work has demonstrated that dendritic/tumor fusion cells induce potent antitumor immune responses in vivo and in vitro. However, little is known about the migration and homing of fusion cells after s.c. injection or the kinetics of CD4+ and CD8+ T cell activation. In the present study, fluorescence-labeled dendritic/MUC1-positive tumor fusion cells (FC/MUC1) were injected s.c. into MUC1-transgenic mice. The FC/MUC1 migrated to draining lymph nodes and were closely associated with T cells in a pattern c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 47 publications
0
48
1
Order By: Relevance
“…Both OK-432 and HSPs are putative ligands of the TLR, stimulate DCs rapidly, and elicit a Th1-promoting phenotype (61,62), all of which are essential for exhibiting capacities to prime naive T cells and develop antitumor CTL responses. Our previous study, which found that depletion of CD4 ϩ T cells significantly impairs CTL induction by DCs/tumor FCs (11,41,63,64), indicates that efficient CTL generation requires the help of CD4 ϩ T cells. Our present study has shown that OK/HS-FCs are superior to other FC preparations for expanding the population of both CD4 ϩ and CD8 ϩ T cells that produce high levels of IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Both OK-432 and HSPs are putative ligands of the TLR, stimulate DCs rapidly, and elicit a Th1-promoting phenotype (61,62), all of which are essential for exhibiting capacities to prime naive T cells and develop antitumor CTL responses. Our previous study, which found that depletion of CD4 ϩ T cells significantly impairs CTL induction by DCs/tumor FCs (11,41,63,64), indicates that efficient CTL generation requires the help of CD4 ϩ T cells. Our present study has shown that OK/HS-FCs are superior to other FC preparations for expanding the population of both CD4 ϩ and CD8 ϩ T cells that produce high levels of IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine production patterns in this study reflect the polyclonal populations of activated T cells rather than the cytokine profile of an individual T cell. 24,41,42 The low level of IL-10 production did not influence the development of specific CTL responses induced by DC/CRCA fusion cells. It was shown that DCs were capable of stimulating T cells to produce IL-10 nonspecifically, and this pattern of production did not influence therapeutic responses.…”
mentioning
confidence: 99%
“…24,40 Both CD4 1 and CD8 1 T cells stimulated by DC/CRCA fusion cells produced IFN-g and were blocked by anti-MHC class I and/or class II MAb, suggesting antigen presentation by fusion cells through MHC class I and class II pathways. The activation of CD4 1 T cells by fusion cells is significant since they play an important role in the induction and maintenance of CTLs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these (Zitvogel et al, 1996;Ashley et al, 1997;Boczkowski et al, 2000;Irvine et al, 2000;Nair et al, 2000;Shimizu et al, 2001;Koido et al, 2002;Chen et al, 2003) have included control DC groups, whereas others have not (Soares et al, 2001). In reports that included a control group of unpulsed DCs, no significant protection was seen with these cells.…”
Section: Discussionmentioning
confidence: 99%